Fluid flow profile in the orthotropic plate+compressible viscous fluid+rigid wall system under the action of the moving load on the plate - Akbarov, Surkay D.; Huseynova, Tarana V. (TECHNO-PRESS, 2020)
The paper studies the fluid flow profile contained between the orthotropic plate and rigid wall under the action of the moving load on the plate and main attention is focused on the fluid velocity profile in the load moving direction. It is assumed that the plate material is orthotropic one and the fluid is viscous and barotropic compressible. The plane-strain state in the plate and the plane flow of the fluid is considered. The motion of the plate is described by utilizing the exact equations of elastodynamics for anisotropic bodies, however, the flow of the fluid by utilizing the linearized Navier-Stokes equations. For the solution of the corresponding boundary value problem, the moving coordinate system associated, with the moving load is introduced, after which the exponential Fourier transformation is employed with respect to the coordinate which indicates the distance of the material points from the moving load. The exact analytical expressions for the Fourier transforms of the sought values are obtained, the originals of which are determined numerically. Presented numerical results and their analyses are focused on the question of how the moving load acting on the face plane of the plate which is not in the contact with the fluid can cause the fluid flow and what type profile has this flow along the thickness direction of the strip filled by the fluid and, finally, how this profile changes ahead and behind with the distance of the moving load.
Keywords: fluid flow profile; orthotropic plate; compressible viscous fluid; moving load; hydro-elastic system; Fourier transform; HYDROELASTIC VIBRATION; FREQUENCY-RESPONSE; FORCED VIBRATION; CIRCULAR PLATES; RIGID WALL; VISCOSITY; DYNAMICS; BODIES; DEPTH; Mechanics